Identification of Human IDO1 Enzyme Activity by Using Genetically Encoded Nitrotyrosine. (27th February 2020) - Zheng, Zhaopeng; Guo, Xuzhen; Yu, Minling; Wang, Xiaoyan; Lu, Hongguang; Li, Fahui; Wang, Jiangyun
Abstract: Human indoleamine 2, 3‐dioxygenase 1 (IDO1) has become an increasingly valuable target for cancer immunotherapy because it promotes immune escape by tumor cells. To date, the function of post‐translational modifications (PTMs) on IDO1 has not been fully elucidated. Among the many forms of PTMs, it has been identified that three tyrosine sites (Y15, Y345, and Y353) on IDO1 are nitrated and play important roles in catalytic function. Herein, by genetically encoding 3‐nitro‐l ‐tyrosine into the tyrosine nitration sites of IDO1, the homogeneous and native nitrated IDO1 have been obtained. It is found that the nitration of different tyrosine sites has different effects on the IDO1 structure and enzyme activity. Nitration at position Y15 has a negligible effect, but nitration at Y345 or Y353 decreases the enzyme activity, especially Y353. Furthermore, these results demonstrate that the regulation of the catalytic function caused by tyrosine nitration is related to perturbation of the protein structure and heme‐binding disruption. Abstract : Site exploration : By genetically encoding 3‐nitro‐l ‐tyrosine (NT) into the tyrosine nitration sites of human indoleamine 2, 3‐dioxygenase 1 (IDO1), it is revealed that the nitration sites have different effects on the structure and enzyme activity of IDO1.